2021
DOI: 10.1007/s11739-021-02786-w
|View full text |Cite
|
Sign up to set email alerts
|

Viral load and disease severity in COVID-19

Abstract: The relationship between COVID-19 severity and viral load is unknown. Our objective was to assess the association between viral load and disease severity in COVID-19. In this single center observational study of adults with laboratory confirmed SARS-CoV-2, the first positive in-hospital nasopharyngeal swab was used to calculate the log10 copies/ml [log10 copy number (CN)] of SARS-CoV-2. Four categories based on level of care and modified sequential organ failure assessment score (mSOFA) at time of swab were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In this research, COVID-19 patients with high SARS-CoV-2 viral load had a greater risk of severe/critical presentation. Some investigations have demonstrated that SARS-CoV-2 viral loads on the upper respiratory tract are positively linked with illness severity, which is consistent with our findings [21][22][23][24]. Others, on the other hand, have found no link [25][26][27].…”
Section: Discussionsupporting
confidence: 92%
“…In this research, COVID-19 patients with high SARS-CoV-2 viral load had a greater risk of severe/critical presentation. Some investigations have demonstrated that SARS-CoV-2 viral loads on the upper respiratory tract are positively linked with illness severity, which is consistent with our findings [21][22][23][24]. Others, on the other hand, have found no link [25][26][27].…”
Section: Discussionsupporting
confidence: 92%
“…It represents a reliable, semi‐quantitative, indicator of the presence viral genetic material inversely correlated to VL. 10 The cut‐off value of CT was 35 (e.g., ≤35 positive/>35 negative) according to manufacturer indications. However, the results of the test were analysed automatically and interpreted by the instrument software with the parameters included in the Assay Protocol.…”
Section: Methodsmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 Although remdesivir shows a significant in vitro activity in terms of reduction of viral load (VL) from respiratory specimens, 7 its effectiveness on clinical outcomes is still matter of debate. 8 In addition, evidences on the correlation between VL and clinical severity are controversial, 9 , 10 , 11 even if it has been shown that patients with more severe disease could present with a slower VL clearance. 7 At present, studies focusing on the effect of remdesivir on VL are few and with contrasting results.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the mean viral load value showed small variability, thereby supporting the power of the current study despite its overall small numbers. The higher viral load value in our study population may be explained with the dominance of the alpha (B.1.1.7) SARS-CoV-2 variant during the enrollment phase (Spring 2021, Germany), which is known to infect the human nasal mucosa more e ciently than the wild-type and has been associated with higher viral load (12,13) . Indeed, the majority of the study subjects carried this variant.…”
Section: Safetymentioning
confidence: 81%
“…The sample size calculation was based on the expected reduction of virus load during the treatment considering 3 treatment arms. It was assumed that all treatment groups present identical baseline virus load at enrolment with a mean value of 5•5 log 10 copies/mL ± 3 SD (12,13) . Since azelastine has been shown to inhibit viral replication by 99•9% in Vero E6 cell culture and in reconstituted human nasal tissue cultures, it was assumed that a reduction of 3-log in virus load would be seen within 3 days in actively treated patients, while no effect on virus load reduction would be seen in placebo treated patients.…”
Section: Discussionmentioning
confidence: 99%